2021
DOI: 10.3390/metabo11040241
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics-Based Comparison of Molecular Compositions of Green, Yellow, and Red Bell Peppers

Abstract: Identifying and annotating the molecular composition of individual foods will improve scientific understanding of how foods impact human health and how much variation exists in the molecular composition of foods of the same species. The complexity of this task includes distinct varieties and variations in natural occurring pigments of foods. Lipidomics, a sub-field of metabolomics, has emerged as an effective tool to help decipher the molecular composition of foods. For this proof-of-principle research, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…However, after processing bell pepper products, waste remains (seeds, peel, stem, and leaves), representing desirable raw material to obtain phytochemical compounds [ 20 ]. They contain diverse bioactive compounds with interesting biological activities (in vivo and in vitro) and applications [ 31 ]. Bioactive compounds are defined as “inherent non-nutrient constituents of food plants with anticipated health-promoting/beneficial and/or toxic effects when ingested” [ 32 ].…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
See 3 more Smart Citations
“…However, after processing bell pepper products, waste remains (seeds, peel, stem, and leaves), representing desirable raw material to obtain phytochemical compounds [ 20 ]. They contain diverse bioactive compounds with interesting biological activities (in vivo and in vitro) and applications [ 31 ]. Bioactive compounds are defined as “inherent non-nutrient constituents of food plants with anticipated health-promoting/beneficial and/or toxic effects when ingested” [ 32 ].…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
“…6-rhamnose 8-glucose (170 µg/g), and Apig. 6-arbinose 8-galactose (151 µg/g) [ 29 , 30 , 31 , 34 , 35 ]; while in red bell pepper, hesperidin (1513 µg/g), catechin (793 µg/g), luteolin 7-glucose (413 µg/g), Apig. 6-rhamnose 8-glucose (314 µg/g), rutin (290 µg/g), quercetin (241 µg/g), and Apig.…”
Section: Phytochemicals Present In Bell Peppersmentioning
confidence: 99%
See 2 more Smart Citations
“…In Capsicum annuum L. cv. Bell pepper, Sutliff et al (2021) reported the presence of 57 glycerophospholipids and glycerolipids compounds in the mature fruits. The selection of fruit color traits could be associated with the modification of nutritional characteristics in bell pepper ( Sutliff et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%